Comparative efficacy and safety of immunotherapies targeting the PD-1/PD-L1 pathway for previously treated advanced non-small cell lung cancer: A Bayesian network meta-analysis. (October 2019) - Almutairi, Abdulaali R.; Alkhatib, Nimer; Martin, Jennifer; Babiker, Hani M.; Garland, Linda L.; McBride, Ali; Abraham, Ivo
Graphical abstract: Highlights: Indirect comparisons yielded no differences in OS and PFS between PD-1/PD-L1 inhibitors in NSCLC. Indirect comparisons showed higher ORR for pembrolizumab and nivolumab relative to atezolizumab. Pembrolizumab ranked 1 st in OS/ORR and OS subgroups: adenoCa, EGFR mutant, ECOG 1, male, age <65y. Nivolumab ranked 1 st in PFS and OS groups: squamous cell disease, EGFR-wild type, ECOG 0. Abstract: Background: Two PD-1 (pembrolizumab, nivolumab) and one PD-L1(atezolizumab) inhibitors are approved for previously treated advanced non-small cell lung cancer but have not been compared in head-to-head trials. Method: A network meta-analysis was conducted to compare efficacy/safety of PD-1/PD-L1 inhibitors. Results: In five-trials (including long-term updates) with docetaxel as common comparator there were no differences in OS and PFS between PD-1/PD-L1 inhibitors. Pembrolizumab (odds ratio(OR) = 2.22, 95%CrI = 1.28–3.70) and nivolumab (OR = 1.92, 95%CrI = 1.15–3.23) had higher ORRs than atezolizumab and at PD-L1 expression ≥50% and ≥1%. Probabilistically, pembrolizumab ranked first in OS and ORR, and in OS sub-analyses for adenocarcinoma, EGFR-mutant, ECOG-score-1, male, and age <65 years. Nivolumab ranked first in PFS, and in OS sub-analyses for squamous-cell disease, EGFR-wild-type, and ECOG-score-0. Pembrolizumab and nivolumab ranked the best option for most of adverse events. Conclusion: While pembrolizumab and nivolumab prevailed in rank in OS and ORR benefit, patient characteristics, safety and tolerance should be considered in treatment decision-making.